Hasan Hanafi, Dialectic of Islamic Thought, and Radical Hermeneutics - Mubarok, Ahmad (TAJDID, 2020)
This article attempts to dismantle Hasan Hanafi's thoughts on the renewal of Islamic thought. This titration analysis study succeeded in revealing that according to Hasan Hanafi there are four main ideas of renewal, revitalizing the classical treasures of Islam, responding to the challenges of Western civilization, seeking revolutionary elements in religion, and creating national integrity in Islam. In addition, according to Hanafi, the term in Islamic theology does not only refer to transcendence and the unseen but also describes the characteristics and empirical scientific methods such as faith, charity, and Imamat. In explaining Islamic theology, Hanafi uses dialectical, phenomenological, and hermeneutical methods.